Phlorotannins and glycolipid metabolism: comprehensive regulatory roles mediated by the gut microbiota - Wu, Shuyan; Sui, Ziqi; Pan, Jie; Men, Xiao; Li, Xiang; Xue, Dongping; Meng, Qingbao; Han, Xionggao; Shen, Yimin (Frontiers in Nutrition, 2026)
Metabolic disorders are precursors to numerous chronic diseases. Phlorotannins is a kind of natural bioactive agents found in brown algae composed with polyphenolic. Due to its role in regulating blood glucose and lipid levels, it is expected to manage chronic metabolic disease. However, previous study has mainly focused phlorotannins on their metabolic effects in the native state. Due to their high molecular weight, these compounds are poorly absorbed in the intestine, which limits their oral bioavailability. This review examines the interactions between phlorotannins and gut microbiota, as well as the role of small-molecule metabolites produced by microbial degradation on host metabolism. Phlorotannins can modulate the composition of the gut microbiota, promote the production of short-chain fatty acids, and increase bile acid metabolism. Therefore, understanding the bioavailability of gut microbiota-derived phlorotannin metabolites is crucial for developing strategies to prevent obesity and manage diabetes.